FLAIR and Diffusion MRI Signals Are Independent Predictors of White Matter Hyperintensities - Maillard, P.; Carmichael, O.; Harvey, D.; Fletcher, E.; Reed, B.; Mungas, D.; DeCarli, C. (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: WMH, associated with cognitive decline and cardiovascular risk factors, may represent only the extreme end of a more widespread continuous WM injury process that progresses during aging and is poorly understood. We investigated the ability of FLAIR and DTI to characterize the longitudinal course of WMH development. MATERIALS AND METHODS: One hundred nineteen participants (mean age, 74.5 ± 7.4), including cognitively healthy elders and subjects diagnosed with Alzheimer disease and mild cognitive impairment, received a comprehensive clinical evaluation and brain MR imaging, including FLAIR and DTI on 2 dates. The risk for each baseline normal-appearing WM voxel to convert into WMH was modeled as a function of baseline FA (model M1) and both baseline FA and standardized FLAIR (M2). Sensitivity, specificity, accuracy, and AUC for predicting conversion to WMH were compared between models. RESULTS: Independent of clinical diagnosis, lower baseline FA (P < .001, both models) and higher baseline FLAIR intensity (P < .001, M2) were independently associated with increased risk for conversion from normal WM to WMH. M1 exhibited higher sensitivity but lower specificity, accuracy, and AUC compared with M2. CONCLUSIONS: These findings provide further evidence that WMH result from a continuous process of WM degeneration with time. Stepwise decreases in WM integrity as measured by both DTI and FLAIR were independently associated with stepwise increases in WMH risk, emphasizing that these modalities may provide complementary information for understanding the time course of aging-associated WM degeneration. ADAlzheimer diseaseAUCarea under the receiver operating characteristic analysis curveCNcognitively healthyFAfractional anisotropyM1first logistic regression modelM2second logistic regression modelMCImild cognitive impairmentMDTminimal deformation templatenFAbaseline normalized FAnFLbaseline normalized FLAIRORodds ratioWMHwhite matter hyperintensities